The Emergence and Struggle against Power System Blackouts - Uspensky, M.; Smirnov, S. (New Visions in Science and Technology Vol. 11, 2021)
Approaches to cascade failure modeling and their consequences are considered; requirements to controlled separation of power systems for the major emergency prevention with possible blackout are presented; existing approaches to its realisation are shown. The power system restoration method after a major emergency with the separation, based on assembly sequence search of its scheme taking into account generation start-up for time is offered.